An analysis of multimodal resources in environmental protection posters - Dallyono, Ruswan; Sukyadi, Didi (Universitas Pendidikan Indonesia, 2019)
Exposure of environmental issues is essential to prevent mass environmental destructions; therefore, campaigns (posters) should be able to activate the viewersâ€™ contemplation on such issues. The emergence of multimodal texts provides a vast opportunity for semioticians to do their analyses in a more creative manner in current communication processes. Accordingly, this study focuses on the interactive meanings of semiotic resources in posters on environmental campaigns using a multimodal perspective. It examines the contribution of visual and textual resources to raise peopleâ€™s awareness on the significance of preserving the environment for future generations. This study drew upon analytical tools from SFL, social semiotics, and reading images (Bezemer Kress, 2008; Kress, 2011; Kress Van Leeuwen 1996; Martinec Salway, 2005).Â This form of contemplation can be considered to be a part of an essential educational process to build a good character. This study shows that the sample posters are significant to represent and transfer environmental messages through these multimodal resources.